A study to find the characteristic imaging findings of various ring-enhancing lesions using MR imaging - V, Ramachandra; Neil Mekala, Indra; Chandra Mataparthy, Anish; Chandra, T. Jaya (International Journal of Medical Research and Review, 2020)
Introduction: Multiple ring-enhancing lesions are one of the most commonly encountered neuroimaging abnormalities. A study was conducted to find the characteristic imaging findings of various ring-enhancing lesions on MRI. Materials and methods: It was a prospective study conducted in the department of radiodiagnosis, GSL Medical College. All age groups of both gender with cerebral ring-enhancing lesions detected in contrast MR studies were taken up for spectroscopy. Patients with a history of claustrophobia and individuals with metallic implants insertion, cardiac pacemakers, and metallic foreign body in situ were excluded. The MRI scan was performed MRI PHILIPS ACHIEVA HDxt 1.5 T, the active shielded superconducting magnet of 1.5telsa magnetic field using SENSE coils for the acquisition of images. Results: Out of 30 study participants, under <45 years category tuberculoma was the common (37%) lesion whereas in >45 years category metastases was common (15%), 44% were female and 56% were males. Depicts T1 signal intensity showed hypointense signal intensity on T1W sequence in 65 (95.5%) cases. Only 4.6% of cases showed isointense signal intensity on T1W image. T2 signal intensity in 73.5% of cases showed hyperintense signal intensity. Conclusions: MRI is an excellent, non-ionizing imaging modality with multiplanar imaging capabilities for excellent grey-white matter differentiation